Improvement of thermal comfort and energy efficiency in historical and monumental buildings by means of localized heating based on non-invasive electric radiant panels. (5th November 2017) - Lodi, Chiara; Magli, Susanna; Contini, Francesco Maria; Muscio, Alberto; Tartarini, Paolo
Highlights: Energy retrofit solutions are presented for historical and monumental buildings. The efficiency of electric radiant heating systems on thermal comfort is analyzed. An operative temperature-based control is applied in a dynamic simulation model. Energy need is reduced while increasing thermal comfort by using electric radiant panels. A high comfort improvement is achieved in the analyzed offices even in the coolest days. Abstract: Energy efficiency and thermal comfort in historic buildings are very often hampered by preservation needs. This issue is particularly relevant for historical and monumental buildings, which currently represent a large part of the historic buildings stock in Europe. For such protected buildings most of the available retrofitting solutions are not feasible and alternatives have to be investigated to guarantee their usability potential. The purpose of this study is therefore to present a methodology to evaluate the potential of electric radiant panels as retrofitting solutions for historical and monumental buildings, focusing on thermal comfort and energy saving potential when compared with conventional fossil-fuel-based heating systems. In fact, the non-invasiveness and flexibility of electrical panels make them one of the few feasible solutions for protected buildings. An original methodology is developed to evaluate the performance of such localized heating systems; the methodology is based on a dynamic simulation model, calibrated with temperature measurements, which takes into account the geometry and technical characteristics of electrical radiant panels and allows different control strategies to be compared. The methodology is applied to a relevant Italian historical building. The results show that the panels, despite their well-known low-exergy efficiency, may become a viable and attractive solution for historical buildings without undermining their preservation requirements. Apart from significantly increasing thermal comfort, electric radiant panels may also allow annual heating energy savings up to 70% for the selected building.